'Bat‐like' choroid plexus and other sonographic features in trisomy 22 at the first trimester of pregnancy. (28th July 2013) - Luchi, Carlo; Monacci, Francesca; Schifano, Martina; Gadducci, Angiolo
Abstract : What's already know about this topic? Abnormalities of the choroid plexus have only been reported in association to holoprosencephaly, so the description of the 'bat sign' in the first trimester is novel and could be important as a marker of some rare chromosomal abnormalities, in this case trisomy 22. What does this study add? Our data is another remarkable proof of the importance of a morphological investigation of the fetus in the first trimester.